Molecular basis for GIGYF-Me31B complex assembly in 4EHP-mediated translational repression. - Peter, D.; Ruscica, V.; Bawankar, P.; Weber, R.; Helms, S.; Valkov, E.; Igreja, C.; Izaurralde, E. (Genes & Development, 2019)
GIGYF (Grb10-interacting GYF [glycine-tyrosine-phenylalanine domain]) proteins coordinate with 4EHP (eIF4E [eukaryotic initiation factor 4E] homologous protein), the DEAD (Asp-Glu-Ala-Asp)-box helicase Me31B/DDX6, and mRNA-binding proteins to elicit transcript-specific repression. However, the underlying molecular mechanism remains unclear. Here, we report that GIGYF contains a motif necessary and sufficient for direct interaction with Me31B/DDX6. A 2.4 Å crystal structure of the GIGYF-Me31B complex reveals that this motif arranges into a coil connected to a ? hairpin on binding to conserved hydrophobic patches on the Me31B RecA2 domain. Structure-guided mutants indicate that 4EHP-GIGYF-DDX6 complex assembly is required for tristetraprolin-mediated down-regulation of an AU-rich mRNA, thus revealing the molecular principles of translational repression.